Level Adoption Of Feed And Organic Fertilizer Technology Based on By Products of Oil Palm Plantation Industry In Lamandau District, Central Kalimantan - Bambang Ngaji Utomo; Ermin Widjaja; Bambang Suharyanto; Yaumil Putri Erlambang; Mohammad Sofyan (Yayasan Ilomata, 2020)
The main problem of livestock raising is feed, for that reason, the government issued an policy about integrated livestock farming with plants/plantations especially oil palm which has the potential to produce feed resources which was abundant, inexpensive, continuous, and does not compete with human needs. The activity was carried out in Lamandau District, Central Kalimantan Province. The objective of the research is to look at the level of adoption of complete feed technology from the by-products of the oil palm plantation industry and organic fertilizer in order to initiate the activities of palm oil - cattle integration. A total of 10 farmer groups, 3 individuals and 1 Livestock Breeding Center of Agriculture services were became cooperators. The business activities of cooperator were include animal husbandry, horticultural crop farming and oil palm plantations. The assessment of the level of adoption is done through interviews, Focus Group Discussions (FGD) and field monitoring, which are classified into 3 criteria, namely low (0.0 - 33.3%), moderate (33.4 - 66.7%) and high (66.8 - 100%). Introduction of technology and accompaniment activities were carried out for 3 years. The FGD activities involved various stakeholders such as the Regional Government, PBS of Palm Oil, Banking, and Farmer Groups. Direct practice is done for farmer group learning. The results of this study showed that in the first year only 1 farmer group adopted feed and organic fertilizer technology. The second-year the level of adoption of cattle feed was 33.33% with the range production of 5-20 tons/month, solid organic fertilizer 33.33% with the ring production of 3-20 tons/month and liquid organic fertilizer (biourine) 33.33% with the range production of 1,000-4,000 liters/month. The third-year the adoption level of cattle feed is 100% with the range production of 1-20 tons/month, 100% solid organic fertilizer with the range production of 1-20 tons/month, and 33.33% liquid organic fertilizer with the range production of 1,000-4,000 liters/month. The conclusion is the adoption of feed technology was greater, followed by organic fertilizer and finally liquid fertilizer technology. This is related to how important is its use in the field. Commitment of local government and PBS of palm oil is needed to help easily and continuously obtain feed and fertilizers materials of palm oil mill byproduct and facilitating marketing of their products.